Enhancements of the refractory submicron aerosol fraction in the Arctic polar vortex: feature or exception ? - Weigel, R; Volk, C. M.; Kandler, K.; Hösen, E.; Günther, Gebhard; Vogel, Bärbel; Grooss, Jens-Uwe; Khaykin, S.; Belyaev, G. V.; Borrmann, S. (EGU, 2014)
In situ measurements with a 4-channel stratospheric condensation particle counter (CPC) were conducted at up to 20 km altitude on board the aircraft M-55 Geophysica from Kiruna, Sweden, in January through March (EUPLEX 2003; RECONCILE 2010) and in December (ESSenCe, 2011). During all campaigns air masses from the upper stratosphere and mesosphere were subsiding inside the Arctic winter vortex, thus transporting refractory aerosol into the lower stratosphere (Θ<500 K) by vertical dispersion. The strength and extent of this downward transport varied between the years depending on the dynamical evolution of the vortex. Inside the vortex and at altitudes of potential temperatures Θ ≥ 450 K as many as eight of eleven particles per cm3 contained refractory material, thermally stable residuals with diameters from 10 nm to a few μm which endure heat exposure of 250 °C. Particle mixing ratios (up to 150 refractory particles per milligram of air) and fractions of non-volatile particles (up to 75% of totally detected particles) reach highest values in air masses with lowest content of nitrous oxide (N2O, down to 70 nmol mol−1). This indicates that refractory aerosol originates from the upper stratosphere or the mesosphere. From mixing ratios of the long lived tracer N2O (simultaneously measured in situ) an empirical index was derived which serves to differentiate air masses according to their origin from inside the vortex, the vortex edge region, and outside the vortex. Previously, observed high fractions of refractory submicron aerosol in the 2003 Arctic vortex were ascribed to unusually strong subsidence during that winter. Measurements under perturbed vortex conditions in 2010 and during early winter in December 2011, however, revealed similarly high values. Thus, the abundance of refractory aerosol at high levels appears to be a feature rather than the exception for the Arctic vortices. During December, the import from aloft into the lower stratosphere appears to be developing; thereafter the abundance of refractory ...